Distinction: A social critique of the judgement of taste - Bourdieu, Pierre 1930-2002 (London Routledge & Kegan Paul Books, 1986)
No judgement of taste is innocent. In a word, we are all snobs. Pierre Bourdieu brilliantly illuminates this situation of the middle class in the modern world. France's leading sociologist focusses here on the French bourgeoisie, its tastes and preferences. Distinction is at once a vast ethnography of contemporary France and a dissection of the bourgeois mind.In the course of everyday life people constantly choose between what they find aesthetically pleasing and what they consider tacky, merely trendy, or ugly. Bourdieu bases his study on surveys that took into account the multitude of social factors that play a part in a Frenchperson's choice of clothing, furniture, leisure activities, dinner menus for guests, and many other matters of taste. What emerges from his analysis is that social snobbery is everywhere in the bourgeois world. The different aesthetic choices people make are all distinctions-that is, choices made in opposition to those made by other classes. Taste is not pure. Bourdieu finds a world of social meaning in the decision to order bouillabaisse, in our contemporary cult of thinness, in the "California sports" such as jogging and cross-country skiing. The social world, he argues, functions simultaneously as a system of power relations and as a symbolic system in which minute distinctions of taste become the basis for social judgement.The topic of Bourdieu's book is a fascinating one: the strategies of social pretension are always curiously engaging. But the book is more than fascinating. It is a major contribution to current debates on the theory of culture and a challenge to the major theoretical schools in contemporary sociology.